Evaluating the relationship between ciprofloxacin prescription and non-susceptibility in Salmonella Typhi in Blantyre, Malawi: an observational study - Ashton, PM; Chunga Chirambo, A; Meiring, JE; Patel, PD; Mbewe, M; Silungwe, N; Chizani, K; Banda, H; Heyderman, RS; Dyson, ZA; MacPherson, P; Henrion, MYR; et al. (Elsevier, 2024)
Background Ciprofloxacin is the first-line drug for treating typhoid fever in many countries in Africa with a high disease burden, but the emergence of non-susceptibility poses a challenge to public health programmes. Through enhanced surveillance as part of vaccine evaluation, we investigated the occurrence and potential determinants of ciprofloxacin non-susceptibility in Blantyre, Malawi.